PENJADWALAN JOB SHOP DENGAN ALGORITMA GENETIKA PADA PT SHIMA PRIMA UTAMA - Sunarni, Theresia; Handy, Handy (Proceedings of KNASTIK, 2012)
PT Shima Prima Utama operate with Job Shop System. Job Shop schedulingfor this company is a scheduling which use a lot of machines and a lot ofoperation with production type make to order. Today its campany has beenusing earliest due date (EDD). It makes completion time for all production(makespan) becomes longer. This is because there are a lot of number ofwork stations (machine) is idle. Base on that situation in this project try togive alternative scheduling method Genetic Algorithm for makespandecreasing. This algorithm is implemented in visual basic encoding byrepresent sequencing of job into the string and arrange it according geneticsimulations. Scheduling with Genetic Algorithm implementation candecrease the makespan as 14.23% from the method before with thesequencing 355333444344443545654536466563621621623-114411135561252526261211122232.